Satisfacción en Estudiantes del Pregrado, en Base a su Percepción de la Calidad Docente - Molina Napuri, Aurora del Carmen (2018)
Based on the study of students’ perception of the undergraduate teaching activity of the Faculty of Administrative Sciences of the National University of San Marcos in the second semester of 2017, which focused on topics such as: knowledge of the subject, attendance and punctuality, ethics, didactic capacity and compliance of the syllabus among others; the presentation of a personalized report to the teacher is proposed, where each one of his students is located in different scenarios, which have been determined through the use of classification and regression trees of data mining. In order to identify patterns through which the teacher is valued (virtues and weaknesses) and thus collaborate with the improvement of the teaching quality of the Faculty.